Multinational corporations as political players. (May 2014) - Léonard, Evelyne; Pulignano, Valeria; Lamare, Ryan; Edwards, Tony
This introductory article to the special issue insists on the need to examine the specific processes and means by which transnational corporations are currently establishing and increasing their power in society. Understanding power and politics in and around multinational corporations requires conceptual and empirical approaches able to address their transnational character, with their action embedded in multiple institutional environments, with hierarchies linking distant headquarters and subsidiaries and involving numerous actors with diverse interests, and with differing industrial relations contexts. Articles in this issue address three key questions: how do transnational corporations leverage their characteristics and organization in support of their own power? How do they interact with the different institutional environments in which they operate, and what power relations do these interactions imply? To what extent do they have the capacity to determine and apply their own rules, independently of established institutional regulations?